ANALYSIS OF GRADUATES' PERCEPTIONS OF AN ACCELERATED BACHELOR OF SCIENCE PROGRAM IN NURSING. - Kemsley, Martha; McCausland, Linda; Feigenbaum, Janice; Riegle, Elizabeth (Journal of Professional Nursing)
Rapid expansion of second-degree programs as one approach to addressing the nursing shortage by increasing the number of graduates in shorter periods of time prompted the need for program evaluation to identify the outcomes, strengths, and best practices of these programs. This study used both quantitative and qualitative methods of inquiry to analyze the responses of 28 of 56 recent graduates of an accelerated baccalaureate program. Respondents rated components of the program from preadmission to graduation on a Likert scale and responded to open-ended questions regarding strengths and weaknesses of the program. Analysis included descriptive statistics for quantitative data and content analysis for qualitative data. The analysis showed a high degree of similarity between the quantitative and qualitative data. Highly rated program components, that is, opportunity for graduate course work and integration with graduate students, clinical skill practice and experiences, variety of teaching methodologies, peer and faculty support, were reflected in the themes of cohort bonding, variety of clinical experiences, and supportive faculty and staff. Outcomes of program satisfaction. National Council Licensure Examination pass rates, successful nursing employment, and graduate school attendance were supported by the data.